(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The study analyzed the impact of the gender gap on the economic growth of the United Arab Emirates for the period (2006-2022). The importance of the study comes from the importance of the impact of gender indicators (the gender gap) on the economic growth of the United Arab Emirates, in order to benefit from them to reduce this gap. In the future, the problem of the study lies in the following question: - Is there an impact of the gender indicator on the economic growth of the United Arab Emirates during the period (2006-2022), while the study aims to demonstrate the impact of gender indicators on the economic growth of the United Arab Emirates during the period (2006-2022). 2022). The hypothesis of the study is that: 1- The study assumes that there is an inverse effect x1 of the gender gap on economic growth in the United Arab Emirates. 2- The study assumes that an increase or decrease in the ratio of the economic participation and employment opportunities index (X2) has a clear positive impact on economic growth in the United Arab Emirates. 3- The study assumes that there is a direct effect x5 of the political empowerment index on economic growth in the United Arab Emirates. The study reached a number of conclusions and recommendations, the most important of which are: 1- The study proved that a positive shock in the rate of economic participation and job opportunities ) lonliness . 2- The study proved that there is a direct effect x5 of political empowerment on economic growth in the Emirates, and the results show that increasing political empowerment by one amount leads to an increase in GDP growth by 1043 units, which is a significant effect at a level less than (0.1), and this explains that Increasing opportunities for political empowerment contributes to spreading the spirit of tolerance, achieving justice, and the individual’s sense of belonging to the homeland. This contributes to increasing the individual’s productivity and thus increasing the growth of the gross domestic product. Based on the conclusions, it recommends the following: 1- It is the responsibility of the United Arab Emirates government to pay special attention to gender gap indicators, especially the political empowerment index of Emirati women, with the aim of increasing women’s participation in political life in this country, and achieving better economic growth in the future. 2- Working to reduce the wage gap between genders in the United Arab Emirates, with the aim of enhancing economic growth in this country. 3- Working to reduce the gender gap in access to digital technology in the United Arab Emirates, with the aim of enhancing economic growth in this country.